Next Generation Sequencing: an Emerging Bioinformatics Field - Jiwan, A; Singh, S (International Journal of Computer Sciences and Engineering, 2025)
DNA sequences are the store house of all the biological information. DNA sequencing focuses on determining the exact order of the nucleotides in a DNA sequence. Many research efforts have been put to the development of cheaper and increasingly higher-throughput sequencing techniques. This lead to development of a massively parallel and efficient method called as Next Generation Sequencing (NGS). The massively parallel NGS technologies have a high throughput with reduced cost. This paper gives a brief working principle of sequencer such as Roche 454 (GS FLX Titanium/GS Junior), Illumina (Genome Analyzer/HiSeq 2000/MiSeq) and Life Technologies (SOLiD/Ion Torrent PGM) along with a their comparison.